Investigation and validation of consumer device accelerometers for the assessment of whole-body vibration. Issue 1 (1st January 2017) - Akinnuli, B.O.; Dahunsi, O.A.; Ayodeji, S.P.; Bodunde, O.P.
Abstract: There exist a discrepancy between the usage of the expensive standard accelerometer and the cheap and accessible consumer device accelerometer for the measurement of whole-body vibration (WBV). This study investigated the validity of accelerations (g-forces) obtained from a consumer device accelerometer by simultaneously using the consumer device accelerometer with a standard accelerometer during evaluation of WBV experienced by earthmoving equipment operators. The consumer device accelerometer is a software (WBV) compatible with iOS devices from operating system 5 and above (LIS331DLH, 3-axis, ±2 g acceleration range, MEMS type) while the standard accelerometer used during this study is a GCDC tri-axial accelerometer (GCDC X16-4 3-Axis, G-Force Data logger, ±18 g acceleration range, MEMS type). The two accelerometers were mounted following the basicentric axes of the seated operators and put on before earthmoving operation. Data from both the accelerometers were analysed using MATLAB. Results gotten from both accelerometers revealed extreme values of WBV. Some fell within the Health Guidance Caution Zone (HGCZ i.e. 0.47 m/s 2 and 0.93 m/s 2 ) while some were above 0.93 m/s 2 . There were however differences between values gotten from the two accelerometers indicating inaccuracy from the consumer device accelerometer. This research created ground for improvement of accelerometers available on mobile devices and perhaps waken the need for developing new and economic methods of WBV measurement and evaluation.